Assessment of Natural Moisture Availability of Turkestan Region of the Republic of Kazakhstan - Gulnar Aldazhanova; Zhumakhan Mustafayev; Askhat Tuletayev; Irina Skorintseva; Amanzhol Kuderin (Indonesian Journal of Geography, 2023)
To increase the level of management efficiency in the agricultural sector of the economy, it is necessary to ensure the implementation of the sustainable environmental management principles, taking into account the spatial patterns of climate change and bioclimatic potential of the territory. The assessment of natural moisture availability of the natural areas of the Turkestan region of the Republic of Kazakhstan for 1941-2020 (by providing a comparative analysis of indicators for 1941-1960 and 2001-2020) was conducted based on the use of the natural moisture coefficient and hydrothermal index or "dryness index" predicated on  energy resources (total of biologically active air temperatures above 10°С, photosynthetically active radiation, evaporating capacity and water consumption of agricultural land). The conducted survey has used the proven domestic, international and proprietary methods according to estimates of natural water availability in the natural areas. The results of a comparative analysis of climatic indices changes in the natural areas of the Turkestan region (by sixteen weather bureau stations) for 1941 to 2020 have shown that there is an increase in average annual air temperatures in all natural areas, and the annual precipitation tends downward which affects the formation of energy resources and natural water supply. The identified features of changes in the natural moisture coefficient and hydrothermal index or "dryness index" in natural area of Turkestan region, make it possible to adjust the spread of its boundaries and consider these changes in the territorial organization of agricultural nature management.